ChemInform Abstract: Recent Progress in the Synthesis and Application of Saddle‐Shaped Cyclooctatetrathiophenes and Their Derivatives. Issue 16 (April 2015) - Zhao, Chunmei; Xu, Li; Wang, Yong; Li, Chunli; Wang, Hua
Abstract Review: 25 refs.